Gender Inequality in Historical Context of The Mahabharata Period: Analysis Through the Sociological Vantage Point - Adhikari, Shukra Raj; Adhikari, Bhawani Shankar; Acharya, Ganga (Paramita: Historical Studies Journal, 2024)
Abstract: Gender is a kind of unit of socio-cultural structure which is always socio-culturally and historically constructed. To identify and analyze gender, historical, social, and cultural structures must be traced from the ancient literary scriptures. The gender study of the ancient time becomes possible only through the history, scriptures, religions, and literature produced in the ancient period. Therefore, the research has focused on identifying and analyzing the gender inequality in the period of The Mahabharata’s social structure. The historical content analysis method has been used to collect and analyze the data to achieve the objective. The gender inequality has been found in the society of The Mahabharata period. Men have been found superior to dominate the women who have been victimized through polygyny and polyandry. The men have been depicted as superior and the women as inferior in the socio-cultural structure of The Mahabharata.  The women seem to be found as whores and as the sexual abuse of the male characters because of the power domination of the patriarchal system in which men have been in the position of resource gaining and resource holding that seems to have been witnessed abundant in The Mahabharata era.  The women are submissive and loyal to their husbands and have been used as commodities by male characters. Such conditions of women characters in the period of The Mahabharata era have been aptly found to be the outcome of the theory of the mode of production and the principle of the patriarchy. Abstrak: Gender merupakan salah satu unit struktur sosial budaya yang senantiasa dikonstruksi secara sosial budaya dan historis. Untuk mengidentifikasi dan menganalisis gender, struktur historis, sosial, dan budaya harus ditelusuri dari kitab suci sastra kuno. Kajian gender pada masa lampau hanya mungkin dilakukan melalui sejarah, kitab suci, agama, dan sastra yang dihasilkan pada masa lampau. Oleh karena itu, penelitian ini difokuskan pada identifikasi dan analisis ketimpangan gender pada periode struktur sosial Mahabharata. Metode analisis isi historis digunakan untuk mengumpulkan dan menganalisis data guna mencapai tujuan. Ketimpangan gender ditemukan dalam masyarakat pada periode Mahabharata. Laki-laki dianggap lebih unggul dalam mendominasi perempuan yang menjadi korban poligami dan poliandri. Laki-laki digambarkan sebagai pihak yang lebih unggul dan perempuan sebagai pihak yang lebih rendah dalam struktur sosial budaya Mahabharata. Perempuan tampaknya ditemukan sebagai pelacur dan sebagai korban pelecehan seksual terhadap tokoh laki-laki karena dominasi kekuasaan sistem patriarki yang menempatkan laki-laki pada posisi sebagai pihak yang memperoleh dan menguasai sumber daya yang tampaknya telah banyak disaksikan pada era Mahabharata. Para wanita tersebut ternyata tunduk dan loyal kepada suami mereka, dan mereka telah dijadikan komoditas oleh tokoh-tokoh laki-laki. Kondisi tokoh-tokoh wanita tersebut pada periode Mahabharata secara tepat telah ditemukan sebagai hasil dari teori cara produksi sekaligus prinsip patriarki.